Accurate Determination, Matrix Effect Estimation, and Uncertainty Evaluation of Three Sulfonamides in Milk by Isotope Dilution Liquid Chromatography-Tandem Mass Spectrometry - Chaonan Han; Xiuqin Li; Hui Jiao; Yan Gao; Qinghe Zhang (Journal of Food Quality)
Liquid chromatography-tandem mass spectrometry (LC-MS/MS) is the most commonly used method for sulfonamide determination. Its accuracy, however, can be affected by many factors. In this study, sulfadiazine (SDZ), sulfadimidine (SMZ), and sulfadimethoxine (SDM) in milk were selected to investigate an accurate determination method and the potential influencing factors in the use of ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Milk samples were extracted by 25 mL perchloric acid solution (pH = 2) and cleaned up using HLB solid-phase extraction (SPE) cartridges. Four kinds of filters, including PTFE, GHP, nylon, and glass fiber, were compared, and PTFE was selected since it had the best recoveries of target sulfonamides (SAs). Three quantitative methods, including external standard (ES), matrix matching (MM), and isotope dilution mass spectrometry (IDMS), were compared, among which IDMS exhibited the best accuracy. The matrix effect under different mobile phase compositions and of different sample matrices were evaluated and discussed. Ion suppression effects were observed during the determination of all SAs, which got stronger with the increase of the methanol composition percent in the mobile phase. After correction by IDMS, the matrix effect could be neglected. Matrix spiked recoveries at three spiked levels (1 μg/kg, 10 μg/kg, and 20 μg/kg) ranged from 96.8% to 103.8% by IDMS. The expanded relative uncertainties were in the range of 2.02% to 5.75%. The method exhibited wide application range, high accuracy, good stability, and high sensitivity.